Keluaran Klinis Pasien Stroke dengan Covid-19 di RSUD Dr. Soedomo Trenggalek pada Tahun 2020 - 2021 - Abdillah, Mi'rajatul; Sholehuddin, Muhammad Afif; Ikhromi, Noryanto; Subroto, Antonius Gatot (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2023)
Introduction: In Indonesia, there is still little data on stroke with COVID-19 patients. COVID-19 patients also experience stroke. This study aims to determine the clinical outcomes of stroke with COVID-19 patients in Trenggalek, Indonesia. Methods: This study used a cross-sectional study design by comparing the clinical outcomes of stroke patients with COVID-19 and stroke patients without COVID-19 at RSUD Trenggalek. The independent variable studied in this study was COVID-19 infection status based on medical records. The study group was subjects with stroke and COVID-19 infection. The control group is subjects with stoke without COVID-19 infection. The dependent variables studied in this study were length of hospitalization, cost of care, and mortality rate. Results: This study found that the average age of patients stroke with COVID-19 was 65 years. Stroke patients with COVID-19 have a higher mortality rate than stroke patients without COVID-19 (p<0.001; 95% CI). The average cost of care in the group of stroke patients with COVID-19 was significantly higher than the stroke group without COVID-19 (p<0.001; CI 95%). However, there was no statistically significant difference in the length of treatment between the control group and the intervention group. (p=0,326). Conclusion: Stroke patients with COVID-19 have higher mortality rates and treatment costs than those without COVID-19. Old age has a higher risk of being infected with the COVID-19 type. However, no significant difference was found in the length of treatment.